1997
DOI: 10.1002/(sici)1099-1395(199701)10:1<42::aid-poc856>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Towards a homologous structural series of solvatochromic ?* indicators

Abstract: Two new π* indicators of solvent dipolarity and polarizability were synthesized and characterized with respect to their solvatochromic and acid‐base properties. The new dyes, N,N‐dipropyl‐p‐nitroaniline and N,N‐dibutyl‐p‐nitroaniline, are part of a homologous structural series of indicators with increasing lipophilic character, ranging from N,N‐dimethyl‐p‐nitroaniline to N,N‐dibutyl‐p‐nitroaniline. The new indicators are designed as specific polarity probes for the characterization of aqueous‐organic interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…89 Helburn and co-workers have investigated indicator dyes in the N,N,dialkyl-4-nitroaniline series. 33,34,91 These workers found that the propyl indicator was most suited for studying SDS micelles, while the butyl, pentyl, and octyl indicators were more compatible with the larger micelles formed by Triton X-114. They postulated that the longer chain probes left the solvent-sensitive nitroaniline group in the aqueous phase, thus not effectively probing the micellar microenvironment of the SDS solution.…”
Section: Physical Basis Of So Lvatochrom Ismmentioning
confidence: 99%
See 1 more Smart Citation
“…89 Helburn and co-workers have investigated indicator dyes in the N,N,dialkyl-4-nitroaniline series. 33,34,91 These workers found that the propyl indicator was most suited for studying SDS micelles, while the butyl, pentyl, and octyl indicators were more compatible with the larger micelles formed by Triton X-114. They postulated that the longer chain probes left the solvent-sensitive nitroaniline group in the aqueous phase, thus not effectively probing the micellar microenvironment of the SDS solution.…”
Section: Physical Basis Of So Lvatochrom Ismmentioning
confidence: 99%
“…12,[15][16][17][18][19][20][21][22][23][24][25][26] This method has also been extended to supercritical uids [27][28][29][30][31] and to organized m edia such as cyclodextrins and micelles. [32][33][34][35][36][37] This paper will describe the basic principles of solvatochromic m ethods, the history of their developm en t, and re cent ap plication s o f these m etho dologies directed towards the understanding of complex local environments.…”
Section: Introductionmentioning
confidence: 99%
“…For consistency in comparison of values, we have re-determined Às for the well characterized small molecule probes (1a-b and 2a) using the same solvent list (Tables 2-4); these values compare favorably with those of Kamlet et al 1 Table 5 summarizes all Às values for indicators in this work computed to date, including some previously published seven-point determinations. 4,8 We suggest that the conformational effects proposed for 1e-f in the solvent mesitylene, which resulted in an outlier point for selected spectral bands ( Fig. 6-1d) on LSERs for those dyes, may also manifest themselves in the region of the LSER that corresponds to v max for linear alkane solvents (p à 0.00).…”
Section: Lsers and Trends In Ssmentioning
confidence: 86%
“…In an earlier paper of this type, 4 we made a strong argument for the N,N-dialkyl-4-nitroanilines as candidate structures for more hydrophobic versions of the p à indicators 1 based on their relatively large values of Às and observed constancy of Às among some of the longer alkyl chain probes. 4 However, an equally strong argument can be made for the 4-alkyloxy nitrobenzenes on the basis of their 'less perturbing' single alkyl chain structure, more constant bandshape, and the constancy of Às over the entire range of carbon-chain lengths. While the phenylether dyes are slightly less sensitive to solvent dipolarity, that is, Às is smaller overall, this drawback may be more than compensated by a spectroscopic behavior that is stable over a wide range of solvent dipolarities and probe alkyl chain lengths.…”
Section: Lsers and Trends In Ssmentioning
confidence: 99%
See 1 more Smart Citation